Pembinaan Pranikah dalam Mencegah Pernikahan Usia Dini - Rofiq, Muhammad Khoirur; Rohman, Muhammad Fathur; Asih, Agustin Fajariah; Fitri, Najma Kamila (Universitas Lampung, 2024)
Indonesia ranks 8th in the world for the phenomenon of early marriage, based on UNICEF data until the end of 2022. In 2022, the Central Bureau of Statistics (BPS) reported that 33.76% of Indonesian youth married for the first time at the age of 19-21. This means that early marriage is still widely practised. Sidorejo Village is one of the villages with a high marriage rate in Warungasem Sub-district, Batang Regency, so early marriage is very possible. Based on the results of the pre-test, the participants' knowledge of early marriage was very low at 70%, so preventive action needs to be taken, namely through premarital coaching. The service aims to find out the participants' understanding of the definition of marriage, the limits of early marriage, the dangers of early marriage, and provide an understanding of marriage, such as marriage preparation, duties and responsibilities, and efforts to prevent early marriage. This service programme uses the Participatory Action Research (PAR) method, where participants are actively involved in every stage of the activity. The implementation is divided into several stages, namely: a) to Know, b) to Understand, c) to Plan, d) to Act, and e) to Change. The activity was attended by 20 participants, including 5 members of the NU Student Association, 5 members of the NU Student Association, and 10 members of the Youth Organisation. Data collection techniques in the form of questionnaires and data analysis techniques Miles and Huberman. The results of the service showed a significant increase in understanding as measured by the comparison of pre-test and post-test results, as well as an increase in participants' understanding of the dangers of early marriage and the steps taken to prevent it.Keywords: divorce; early marriage; marital bonding, marriage readiness; premarital coaching AbstrakIndonesia menempati posisi ke-8 di dunia atas fenomena pernikahan dini, berdasarkan data UNICEF hingga akhir tahun 2022. Pada tahun 2022, Badan Pusat Statistik (BPS) melaporkan bahwa sebanyak 33,76% pemuda Indonesia menikah untuk pertama kalinya pada usia 19-21 tahun. Artinya, pernikahan dini masih banyak dilakukan. Desa Sidorejo menjadi salah satu desa dengan tingkat pernikahan tinggi di Kecamatan Warungasem, Kabupaten Batang sehingga sangat dimungkinkan terjadi pernikahan dini. Berdasarkan hasil pre test, pengetahuan peserta tentang pernikahan dini sangat rendah yakni sebesar 70% sehingga perlu dilakukan tindakan preventif, yakni melalui pembinaan pranikah. Pengabdian bertujuan, mengetahui pemahaman peserta mengenai pengertian pernikahan, batasan pernikahan usia dini, bahaya pernikahan usia dini, serta memberikan pemahaman tentang pernikahan, seperti persiapan pernikahan, tugas dan tanggung jawab, dan upaya mencegah pernikahan dini. Program pengabdian ini menggunakan metode Participatory Action Research (PAR), di mana peserta terlibat aktif dalam setiap tahap kegiatan. Pelaksanaan dibagi menjadi beberapa tahap, yakni: a) to Know, b) to Understand, c) to Planning, d) to Act, dan e) to Change. Kegiatan dihadiri 20 peserta mencakup 5 anggota Ikatan Pelajar NU, 5 anggota Ikatan Pelajar Putri NU, dan 10 angggota Karang Taruna. Teknik pengumpulan data berupa kuesioner dan teknik analisis data Miles and Huberman. Hasil pengabdian menunjukkan peningkatan pemahaman yang signifikan yang diukur melalui perbandingan hasil pre test dan post test, serta peningkatan pemahaman peserta terkait bahaya pernikahan dini dan langkah-langkah yang diambil untuk mencegahnya.Kata Kunci: ikatan perkawinan; kesiapan pernikahan; pembinaan pranikah; perceraian; pernikahan dini